Evaluating the Balance between Quality and Quantity in Secondary Education in Tanzania: Challenges and Opportunities - Peter Mduwile; Dulumoni Goswami; Didymus Ibrahim; Janeth Lufunga; Niharika Baruah (Journal of Education for Sustainable Development Studies, 2025)
Tanzania has expanded secondary education access over the past two decades through initiatives like the Secondary Education Development Program and Free Education Policy. While these reforms have significantly increased enrollment, concerns about educational quality persist. This study investigates how rapid enrollment growth has affected the quality of secondary education in Tanzania, particularly focusing on disparities in learning outcomes, teacher distribution, and infrastructure. A mixed-methods design was employed, combining quantitative analysis of government statistics (2015–2023) with qualitative data from interviews and focus group discussions in both urban and rural schools. Quantitative data assessed trends in enrollment, teacher-pupil ratios, and academic performance, while qualitative insights explored experiences of students, teachers, and administrators. Enrollment rose by over 50% between 2015 and 2023. However, this expansion coincided with overcrowded classrooms, underqualified teachers, and limited resources. Teacher deployment and learning outcomes remained uneven across regions. Participants highlighted systemic challenges, including a lack of functional laboratories, insufficient materials, and poor infrastructure. Despite these issues, emerging opportunities include ICT integration, community engagement, donor support, and reforms in the Education and Training Policy. Tanzania’s focus on universal access must be matched by targeted efforts to enhance quality. Key recommendations include investing in teacher training, infrastructure development, equitable resource allocation, digital learning, and accountability mechanisms. Achieving Sustainable Development Goal 4 requires a strategic balance between quantity and quality to ensure inclusive, equitable, and transformative education for all.